Revision of the genus Nephelomilta Hampson, 1900, with descriptions of twelve new species and two new subspecies (Lepidoptera, Erebidae, Arctiinae) - Volynkin, Anton V.; Černý, Karel (Zootaxa, 2018)
The genus Nephelomilta Hampson, 1900 is revised. The genus Kailasha Singh & Kirti, 2015 is synonymized with Nephelomilta. Twelve new species, N. admiranda, sp. nov. (NE India), N. kanchenjunga, sp. nov. (NE India), N. wolfgangspeideli, sp. nov. (S Vietnam), N. ranau, sp. nov. (Sumatra), N. bana, sp. nov. (C Vietnam), N. martini, sp. nov. (N Vietnam), N. thomaswitti, sp. nov. (Nepal, NE India), N. fangae, sp. nov. (China: Hainan), N. hortensis, sp. nov. (N Thailand), N. melli, sp. nov. (E and S China), N. ferruginea, sp. nov. (Sumatra) and N. diehli, sp. nov. (Sumatra), and two new subspecies, N. sumatrana effractoida, ssp. nov. (N India and Indochina) and N. hortensis fansipana, ssp. nov. (N Vietnam) are described. Barsine fuscobarsine, 2016 is synonymized with Nephelomilta suffusa (Hampson, 1891). Eleven new combinations are established and three taxa previously treated as junior synonyms of N. effracta are upgraded to species level: N. taprobana (Hampson, 1901), comb. nov., N. sumatrana (van Eecke, 1927), comb. & stat. nov., N. gulmargensis (N. Singh, Kirti & D.P. Singh, 2015), comb. nov., N. effracta (Walker, 1854), comb. nov., N. pseudoeffracta (Kirti, Joshi & N. Singh, 2013), comb. nov., N. klapperichi (Daniel, 1952), comb. nov., N. pellucida (Rothschild, 1936), comb. nov., N. babensis (Bae & Bayarsaikhan, 2017), comb. nov., N. karenkonis (Matsumura, 1930), comb. & stat. nov., N. angkorensis (Bayarsaikhan & Bae, 2016), comb. nov., N. pusilla (Wileman, 1910), comb. & stat. nov. Lectotypes for Chionaema effracta sumatrana van Eecke, 1927, Chionaema pellucida Rothschild, 1936 and Chionaema pusilla Wileman, 1910 are designated.